Phloem loading in cucumber: combined symplastic and apoplastic strategies. (12th February 2019) - Ma, Si; Sun, Lulu; Sui, Xiaolei; Li, Yaxin; Chang, Ying; Fan, Jingwei; Zhang, Zhenxian
Summary: Phloem loading, as the first step of transporting photoassimilates from mesophyll cells to sieve element‐companion cell complex, creates a driving force for long‐distance nutrient transport. Three loading strategies have been proposed: passive symplastic loading, apoplastic loading and symplastic transfer followed by polymer‐trapping of stachyose and raffinose. Although individual species are generally referred to as using a single phloem loading mechanism, it has been suggested that some plants may use more than one, i.e. 'mixed loading'. Here, by using a combination of electron microscopy, reverse genetics and 14 C labeling, loading strategies were studied in cucumber, a polymer‐trapping loading species. The results indicate that intermediary cells (ICs), which mediate polymer‐trapping, and ordinary companion cells, which mediate apoplastic loading, were mainly found in the fifth and third order veins, respectively. Accordingly, a cucumber galactinol synthase gene ( CsGolS1 ) and a sucrose transporter gene ( CsSUT2 ) were expressed mainly in the fifth/third and the third order veins, respectively. Immunolocalization analysis indicated that CsGolS1 was localized in companion cells (CCs) while CsSUT2 was in CCs and sieve elements (SEs). Suppressing CsGolS1 significantly decreased the stachyose level and increased sucrose content, while suppressing CsSUT2 decreased the sucrose level and increased the stachyose content in leaves. After 14 CO2 labeling, [ 14 C]sucrose export increased and [ 14 C]stachyose export reduced from petioles in CsGolS1i plants, but [ 14 C]sucrose export decreased and [ 14 C]stachyose export increased into petioles in CsSUT2i plants. Similar results were also observed after pre‐treating the CsGolS1i leaves with PCMBS (transporter inhibitor). These results demonstrate that cucumber phloem loading depends on both polymer‐trapping and apoplastic loading strategies. Significance Statement: This study demonstrates a mixed‐loading strategy (active symplastic and apoplastic strategies) in cucumber leaves based on the ultrastructure of companion cells, 14 C labeling and reverse genetics, and provides comprehensive evidence from physiology and molecular biology that the apoplastic loading pathway is present in a putative symplastic phloem loader.